Neo-Colonialism in Ngugi wa Thiong’o’s Devil on the Cross and Ferdinand Oyono’s The Old Man and the Medal - Ikechi, Emeka; Angaye, Tarikiye E. (NIU Journal of Humanities, 2020)
This study will critically examine the issues of alienation and disillusionment, which results in the economic down-turn of most African nations after independent and to date because of mismanagement and lack of proper control of endowed resources. Neo-colonialism is one of the foremost contemporary focuses of the twenty-first century literary discourse. It is an alternative and new artistic explorative mechanism, for the fact that it centres on the socio-economic realities and leadership styles of African rulers, which portrays the disregard of fellow Africans. Earlier studies concentrate on the concerns of the use of language, identity crisis and forceful acquisition of natural resources, which provided the platform of the different forms of revolutionary experiences against the colonial administration. The theoretical approach to the study hinges on the post colonialism as a theory and a period that echoes the African culture and sensibilities. The objective of the study is to show the disappointment and agony of the teeming mass of the continent in the post-colonial and modern periods. The study will assist in expanding scholarship of representation in postcolonial and contemporary African literary discourse. Keywords: disillusionment, exploration, leadership, alienation, sensibilities.